2021
DOI: 10.1186/s12883-021-02214-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in comorbidities and risk factors in ischemic stroke patients with a history of atrial fibrillation

Abstract: Background Atrial Fibrillation (AF) is a common cardiac arrhythmia and has been identified as a major risk factor for acute ischemic stroke (AIS). Gender differences in the disease process, causative mechanisms and outcomes of AF have been investigated. In the current study, we determined whether there is a gender-based disparity in AIS patients with baseline AF, and whether such a discrepancy is associated with specific risk factors and comorbidities. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In addition, we found that the women in our study had a higher prevalence of stroke than men. Generally, women older than 65 years with AF have a higher rate of ischaemic strokes than men with AF [ 29 , 39 , 40 ], and our results may indicate that women in Greenland more often suffer a stroke before being diagnosed with AF.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, we found that the women in our study had a higher prevalence of stroke than men. Generally, women older than 65 years with AF have a higher rate of ischaemic strokes than men with AF [ 29 , 39 , 40 ], and our results may indicate that women in Greenland more often suffer a stroke before being diagnosed with AF.…”
Section: Discussionmentioning
confidence: 87%
“…Similar findings have been reported for AIS patients with histories of previous TIA, [21][22][23] elevated cholesterol levels, 13,24 and direct admission. 25,26 We also observed that AIS patients without HF who did not receive rtPA were more likely to be Hispanic and present with coronary artery stenosis, previous stroke, and elevated lipid level, creatinine, INR, and heart rate. Our finding that Hispanic AIS patients without HF were more likely not to be treated with rtPA is supported by prior studies showing lower rates of rtPA use among the Hispanic population.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, the current study did not find any significant sex differences in the other stroke risk factors. Significant gender differences in stroke risk factors, such as hypertension, 15 , 43 , 44 atrial fibrillation, 44 , 49 dyslipidemia, and obesity, 43 , 44 have been reported in several studies. These are more common in women than in men.…”
Section: Discussionmentioning
confidence: 99%